Path Planning for Underactuated Dubins Micro-robots Using Switching Control - An, Y.; Xu, C.; Lin, Qun; Loxton, Ryan; Teo, Kok Lay (IEEE, 2013)
In this paper, we develop an optimal path planning strategy for under-actuated Dubins micro-robots. Such robots are non-holonomic robots constrained to move along circular paths of fixed curvature clockwise or counter-clockwise. Our objective is to investigate the coverage and optimal path problems, as well as multi-robot cooperation, for a switching control scheme. Our methods are based on elementary geometry and optimal control techniques. The results in this paper show that the trajectories of micro-robots can cover the entire two-dimensional plane, and that the proposed switching control scheme allows multiple robots to cooperate. In addition, we deduce the minimum-time path under the switching control scheme by converting the robot model into the traditional Dubins vehicle model.